Drivers and barriers to agroforestry adoption among forest farmers: A systematic review - Qonita Hasna’ul Aini (Institute for Advanced Social, Science, and Sustainable Future, 2026)
Background: Agroforestry is widely promoted as a sustainable land-use system that addresses poverty, environmental degradation, and climate change. Despite its strategic role, adoption among forest farmer groups remains limited, indicating a gap between policy ambition and field-level implementation. Identifying the determinants influencing adoption decisions is therefore essential to improve intervention strategies. Methods: This study applies a systematic literature review of empirical publications from 2020–2025. Selected studies were synthesized to identify key determinants of agroforestry adoption, organized into four analytical pillars: economic, socio-cultural, institutional, and ecological factors. Findings: Agroforestry adoption emerges as a multifaceted decision shaped by interacting structural and contextual factors. Economically, income diversification and market access act as major incentives, though high initial costs and delayed returns constrain uptake. Socio-cultural factors, particularly farmer group participation, education, and social capital, significantly increase adoption likelihood. Institutional support—especially secure land tenure under Social Forestry programs and access to extension services—plays a decisive enabling role. Ecological pressures, including land degradation and soil erosion, frequently trigger transitions toward agroforestry as a resilience strategy. These determinants operate interdependently rather than independently. Conclusion: Effective agroforestry promotion requires integrated policies that simultaneously address economic viability, social capacity, institutional support, and ecological conditions. A holistic support ecosystem is needed to position farmers as active agents of sustainable land transformation. Novelty/Originality of this article: This review synthesizes recent empirical evidence into a four-pillar analytical framework, conceptualizing agroforestry adoption as a dynamic and systemic process, and providing a structured basis for more coherent, evidence-based policy design.